2022
DOI: 10.1371/journal.pgph.0000744
|View full text |Cite
|
Sign up to set email alerts
|

Mortality rate and cause among people with intellectual disabilities in South Korea: A nationwide representative cross-sectional study from 2015 to 2019

Abstract: People with intellectual disabilities (ID) age faster and have a higher prevalence of degenerative diseases. The aim of this study was to identify the patterns/ causes of death among people with ID. We conducted a nationwide, retrospective, cross-sectional study of people with ID in South Korea. The database was compiled by merging data of people registered with ID, based on the 2015–2019 Standards from the Ministry of Health and Welfare, with the cause of death data published by the Korea National Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…They have a shorter life expectancy and mostly die at young ages (Glover et al 2017). Cardiovascular and respiratory diseases and neoplasms are the most common causes of death in adults with IDDs (Patja et al 2001;Glover et al 2017;Trollor et al 2017;O'Leary et al 2018;Cooper et al 2020;Shooshtari et al 2020;Kim et al 2022). A US national survey has reported that heart disease is the leading cause of death in adults with IDDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have a shorter life expectancy and mostly die at young ages (Glover et al 2017). Cardiovascular and respiratory diseases and neoplasms are the most common causes of death in adults with IDDs (Patja et al 2001;Glover et al 2017;Trollor et al 2017;O'Leary et al 2018;Cooper et al 2020;Shooshtari et al 2020;Kim et al 2022). A US national survey has reported that heart disease is the leading cause of death in adults with IDDs.…”
Section: Introductionmentioning
confidence: 99%
“…2020; Kim et al . 2022). A US national survey has reported that heart disease is the leading cause of death in adults with IDDs.…”
Section: Introductionmentioning
confidence: 99%